2018
DOI: 10.1093/arclin/acy074
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Towards a Cultural Neuropsychology Assessment Decision-Making Framework: Comparison of WAIS-IV Norms from Colombia, Chile, Mexico, Spain, United States, and Canada

Abstract: Objective Test and normative data selection in cross-cultural neuropsychology remain a complex issue. Despite growing awareness, more studies and instruments are needed to adequately address the impact of cultural factors, such as quantity and quality of education. In this study, we examine the interpretive effects of applying six relevant WAIS-IV norms to a Colombian sample. Method A sample of 305 highly educated Colombian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 138 publications
(248 reference statements)
0
14
0
3
Order By: Relevance
“…Furthermore, attempts to apply the same norms across populations without accounting for cultural and linguistic variations will result in detrimental ethical dilemmas such as clinical misdiagnosis and inaccurate conclusions for research studies. Duggan et al (2019) exemplified this in a study that demonstrated the highly variable effects of using normative Wechsler Adult Intelligence Scale 4th edition data derived from six different countries, with up to an 11-18 point FSIQ/Index score discrepancy depending on the population-derived normative data used. As a result, it is challenging to merge data from diverse communities to investigate research questions of global clinical significance, such as potential risk factors for neurodegenerative disorders and post-COVID-19 cognitive outcomes.…”
mentioning
confidence: 95%
“…Furthermore, attempts to apply the same norms across populations without accounting for cultural and linguistic variations will result in detrimental ethical dilemmas such as clinical misdiagnosis and inaccurate conclusions for research studies. Duggan et al (2019) exemplified this in a study that demonstrated the highly variable effects of using normative Wechsler Adult Intelligence Scale 4th edition data derived from six different countries, with up to an 11-18 point FSIQ/Index score discrepancy depending on the population-derived normative data used. As a result, it is challenging to merge data from diverse communities to investigate research questions of global clinical significance, such as potential risk factors for neurodegenerative disorders and post-COVID-19 cognitive outcomes.…”
mentioning
confidence: 95%
“…), it is important to develop diagnostic tests of "intercultural neuropsychology". In this case, neuropsychologists use interpretation tests WAIS-IV, which include six relevant parameters (Duggan et al, 2019). Theoretical generalizations of this study can help improve the diagnosis of effectiveness and implementation of cultural neuropsychological decision-making system.…”
Section: Discussionmentioning
confidence: 94%
“…Following the perspective of the Greenwich IQ, differences in average IQ between nations will be reflected in the standardization of intelligence tests, i.e., the IQ scale will have different psychological meaning for different countries. For instance, a Latin-American study (Duggan, Awakon, Loaiza, & Garcia-Barrera, 2019) conducted on a sample of 305 highly educated Colombian corporate executives, made a comparison in the WAIS-IV norms from Colombia, Chile, Mexico, Spain, United States, and Canada. One of their results is relevant for the present paper.…”
Section: The International Test Commission (2018) and The American Ementioning
confidence: 99%
“…The authors concluded there is an American-European assessment bias in cross-cultural test standardizations. Duggan et al (2019) have the merit in presenting results, for the first time, regarding Latin American mean IQ differences through several norms of the Wechsler scales. However, is not clear as to why there was the highest agreement between the classifications Colombia/USA was observed in the Verbal Comprehension Index (52%), supposedly an index more sensitive to cultural/linguistic influence.…”
Section: The International Test Commission (2018) and The American Ementioning
confidence: 99%